Analysis of The Factors That Contribute To The High Rate of Private Vehicle Ownership In DKI Jakarta - Lode Wijk Pandapotan Girsang (Mahadi: Indonesia Journal of Law, 2023)
One of the primary causes of traffic jams in Daerah Khusus Ibu kota (DKI) Jakarta is the high number of private vehicle ownership. The DKI Jakarta government has implemented a number of measures to reduce motorized vehicles, such as the "ganjil-genap" policy, progressive tariffs, and the provision of various forms of public transit as an alternative, to alleviate congestion. However, these efforts have not been able to reduce the number of private vehicle ownership in DKI JakartaThis study adopted qualitative research approach by utilizing the literature study methodology. The results shows that the high rate of private vehicle ownership in DKI Jakarta is caused by several factors: first, there are still loopholes for committing violations in every policy implemented by the DKI Jakarta government. Second, that private vehicle ownership is not just a means of transportation, but also a way of showing social class in people's lives. Third, the DKI Jakarta administration has not been able to offer public transportation that satisfies people's needs: safe, able to integrate all modes of transportation, as well as simple accessibility and the capacity to send passengers to their final destination.